Deteksi dini faktor risiko penyakit tidak menular melalui edukasi dan skrining kesehatan pada petugas kebersihan kampus di Makassar - Sigit Dwi Pramono; Berry Erida Hasbi; Suci Noviyanah Ansary (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Early detection of non-communicable disease risk factors through health education and screening among campus cleaning staff in Makassar. Non-communicable diseases are the leading cause of death worldwide and in Indonesia, yet cleaning staff as support workers in higher education institutions are rarely targeted by early detection programmes. This community service activity aimed to detect non-communicable disease risk factors early and to deliver health education to cleaning staff at the Faculty of Medicine, Universitas Muslim Indonesia, Makassar. Conducted on 29 August 2025 using a participatory approach, it comprised three integrated stages: group health education, health screening, and individual counselling. Screening covered body weight, height, waist circumference, blood pressure, random blood glucose, and total cholesterol. All cleaning staff on duty were enrolled by total sampling, and the data were analysed descriptively. Of the 36 participants, 32 (88.9%) were women, with a mean age of 42.6 ± 11.9 years, and 23 (63.9%) had completed junior secondary education or less. Obesity was found in 18 participants (50.0%) and overweight in 8 (22.2%). Central obesity was identified in 23 participants (63.9%), comprising 21 of 32 women (65.6%) and 2 of 4 men (50.0%). Suboptimal blood pressure was found in 25 participants (69.4%), of whom 16 (44.4%) met the criteria for hypertension. Five participants (13.9%) were prediabetic and 3 (8.3%) diabetic, while 4 (11.1%) had borderline total cholesterol. All participants with abnormal results received counselling and referral to primary health care. These findings confirm a high burden of non-communicable disease risk factors among cleaning staff, particularly women.